Konversi Limbah Budidaya Ikan Sistem Intensif Menjadi Biogas Skala Rumah Tangga - Andini, Andini; Cahya, Anindya; Ningsih, Ayu Oktavia; Iqbal, Muhammad; Sugiarti, Sri; Fitrani, Mirna (Seminar Nasional Lahan Suboptimal, 2021)
Andini A, Cahya A, Ningsih AO, Iqbal M, Sugiarti S, Fitrani M.  2021. Intensive system fish farming waste conversion to biogas household scale. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 400-410.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Intensive system fish farming with high protein artificial feeding in a limited scope produces waste that can negatively impact if it is directly discharged to the waters. This study aimed to examine whether intensive fish farming waste can be converted into biogas, especially on a household scale, as an alternative in processing aquaculture waste. The method used by the researcher in the literature review method is due to the Covid-19 pandemic situation, which limits researchers from taking data. The results of the literature study state that aquaculture waste has the potential for methanogenic bacteria as the main component of biogas with an anaerobic decomposition process. The content of nitrogen (N2) and hydrogen sulfide (H2S) in aquaculture waste is also an additional component in biogas production. Household-scale biogas production was formed on day 4‒30 which consists of several processes such as hydrolysis, acetogenesis, acetogenesis, and methanogenesis. Biogas production results from fish farming waste can also be used as organic fertilizer for plants or agricultural land. Therefore, converting fish farming waste into biogas can be done as an effort to treat aquaculture waste. Suggestions from this research are necessary to re-examine directly in producing biogas to obtain more relevant data.